Targeting bone homeostasis regulation: potential of traditional Chinese medicine flavonoids in the treatment of osteoporosis - Du, Jiazhe; Wang, Yincang; Wu, Chengliang; Zhang, Xinyu; Zhang, Xiaofeng; Xu, Xilin (Frontiers in Pharmacology, 2024)
Osteoporosis is a systemic metabolic disease characterized by disrupted bone formation/resorption and homeostasis. Flavonoids extracted from traditional Chinese medicinal plants regulate bone homeostasis by intervening in differentiating bone marrow mesenchymal stem cells, balancing the bone immune system, inhibiting oxidative stress response, and reversing iron overload. The target molecules and signaling pathways, such as Wnt/β-catenin and OPG/RANKL/RANK, directly affect osteoblast/osteoclast activity, exhibiting significant potential in the treatment of OP.Therefore, this study presents a systematic review of the recent literature to provide comprehensive information on the traditional Chinese medicine flavonoids involved in the regulation of bone homeostasis. Also, the molecular mechanisms and pharmacological uses of these metabolites are summarized, and their clinical translation and development potential are discussed.